Nature Pet's House - Rocky, Nur Aisya; Che Ani, Nurul Syafiqah; Mohd Sani, Nurainaa Insyira; Hamid, Nor Baizura (Multidisciplinary Applied Research and Innovation, 2025)
The Nature Pet's House project combines pet care with sustainable practices, emphasizing cleanliness, energy efficiency, and cost savings through the use of natural odor-control materials and solar energy. This study aims to create a clean, environmentally friendly, and cost-effective environment for pets by using organic materials and renewable energy sources. Methodologically, the study used surveys to collect data on the preferences of pet owners and conducted tests using equipment to assess the effectiveness of materials and energy sources on the developed model. The results of the questionnaire analysis showed a significant acceptance and preference for natural odor-control materials such as charcoal among the respondents, which was 47% of the total number of respondents of 100 people. Of those surveyed, 51%–75% agreed that charcoal is an effective way to reduce pet odors. The project lowers operating expenses and increases energy efficiency in the pet care industry by utilizing solar energy. The technique measured voltage and current using a multimeter. The electric voltage and current produced by the Nature Pet's House model were 12.42 V and 2.85 A, respectively. Based on the findings, it is evident that using charcoal has benefits, including enhancing pet comfort and owner satisfaction while having a less negative environmental impact. The project's main objective is to explore how integrating eco-friendly technologies could enhance pet care and promote sustainable practices.